2021
DOI: 10.1042/cs20210259
|View full text |Cite
|
Sign up to set email alerts
|

Dihydromyricetin ameliorates vascular calcification in chronic kidney disease by targeting AKT signaling

Abstract: Vascular calcification is highly prevalent in chronic kidney disease (CKD), and characterized by trans-differentiation from contractile vascular smooth muscle cells (VSMCs) into an osteogenic phenotype. However, no effective and therapeutic option to prevent vascular calcification is yet available. Dihydromyricetin (DMY), a bioactive flavonoid isolated from Ampelopsis grossedentata, has been found to inhibit VSMCs proliferation and the injury-induced neointimal formation. However, whether DMY has an effect on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 55 publications
(52 reference statements)
1
6
0
Order By: Relevance
“…Whether DHM exhibits a protective role against CAVD progression in humans requires further study. Our present study demonstrated that DHM prevents the osteogenic differentiation of hVICs via a c-KIT/IL-6dependent pathway at noncytotoxic concentrations of 20 μM, as evidenced by decreased protein levels of two osteogenesisspecific genes (ALP and Runx2) and calcified nodule formation, which is consistent with several previous findings involving the protective role of DHM in atherosclerosis and vascular calcification (Liu et al, 2017;Yang et al, 2020;Feng et al, 2021). In addition, a recent study indicated that DHM significantly suppressed foam cell formation by regulating cholesterol efflux in macrophages (Zeng et al, 2018), thereby protecting ApoE −/− mice from atherosclerosis.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Whether DHM exhibits a protective role against CAVD progression in humans requires further study. Our present study demonstrated that DHM prevents the osteogenic differentiation of hVICs via a c-KIT/IL-6dependent pathway at noncytotoxic concentrations of 20 μM, as evidenced by decreased protein levels of two osteogenesisspecific genes (ALP and Runx2) and calcified nodule formation, which is consistent with several previous findings involving the protective role of DHM in atherosclerosis and vascular calcification (Liu et al, 2017;Yang et al, 2020;Feng et al, 2021). In addition, a recent study indicated that DHM significantly suppressed foam cell formation by regulating cholesterol efflux in macrophages (Zeng et al, 2018), thereby protecting ApoE −/− mice from atherosclerosis.…”
Section: Discussionsupporting
confidence: 93%
“…Mounting evidence suggests that DHM exhibits cardiovascular protective properties in cardiovascular diseases, such as vascular calcification ( Feng et al, 2021 ), endothelial protection ( Chen et al, 2021 ), and pulmonary arterial hypertension ( Li Q et al, 2017 ). In atherosclerosis, which shares similar pathological features with CAVD ( Kostyunin et al, 2020 ), DHM has been shown to increase endothelial nitric oxide production in apolipoprotein E-deficient mice (ApoE −/− ) ( Yang et al, 2020 ) and protect human umbilical vein endothelial cells from oxidative damage ( Zhang et al, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The VC model was performed as described previously. 7 , 8 , 22 In brief, rats were anaesthetized with sodium pentobarbital (50 mg/kg) via intraperitoneal injection. Subsequently, a 2/3 right nephrectomy was performed, followed by the complete removal of the left kidney a week later to induce CKD.…”
Section: Methodsmentioning
confidence: 99%
“…Primary rat VSMCs were obtained from the thoracic aortas of 2-month-old male Sprague-Dawley rats using the explant method detailed in our prior studies. 7 , 8 , 22 In brief, the rats were euthanized intraperitoneally with sodium pentobarbital (150 mg/kg) for aortic isolation. The aortas were dissected, longitudinally opened with sterile scissors, and then segmented into small pieces under sterile conditions.…”
Section: Methodsmentioning
confidence: 99%